Cell-autonomous and non-autonomous growth-defective mutants of Drosophila melanogaster. - Galloni, M.; Edgar, B.A. (Development, 1999)
During animal development, growth of the various tissues and organs that make up the body must be coordinated. Despite recent progress in understanding growth control within the cell unit, the mechanisms that coordinate growth at the organismal level are still poorly understood. To study this problem, we performed a genetic screen for larval growth-defective mutants in Drosophila melanogaster. Characterization of these mutants revealed distinct types of larval growth defects. An allelic series for the translation initiation factor, Eif4A, showed different growth rates and suggests that Eif4A could be used as a dose-dependent growth regulator. Two mutants that fail to exit cellular quiescence at larval hatching (milou and eif4(1006)) have a DNA replication block that can be bypassed by overexpression of the E2F transcription factor. A mutation (bonsaï) in a homolog of the prokaryotic ribosomal protein, RPS15, causes a growth defect that is non-cell-autonomous. Our results emphasize the importance of translational regulation for the exit from quiescence. They suggest that the level of protein synthesis required for cell cycle progression varies according to tissue type. The isolation of non-cell-autonomous larval growth-defective mutants suggests that specialized organs coordinate growth throughout the animal and provides new tools for studies of organismal growth regulation.